2016
DOI: 10.3390/catal6060086
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Electrocatalysts Based on Coupled Iron Nitride Nanoparticles with Nitrogen-Doped Carbon

Abstract: Aimed at developing a highly active and stable non-precious metal electrocatalyst for oxygen reduction reaction (ORR), a novel Fe x N y /NC nanocomposite-that is composed of highly dispersed iron nitride nanoparticles supported on nitrogen-doped carbon (NC)-was prepared by pyrolyzing carbon black with an iron-containing precursor in an NH 3 atmosphere. The influence of the various synthetic parameters such as the Fe precursor, Fe content, pyrolysis temperature and pyrolysis time on ORR performance of the prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In this respect, enormous viable noble-metal-free catalysts (Fe, Co, etc.) [6,7], or metal oxide [8], sulphide [9], nitride [10], carbide [11], metal-free carbon based materials [12] and nitrogen-doped carbon [13] have been actively pursued. Among above mentioned catalysts, the application of iron oxide as the electrocatalyst is…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, enormous viable noble-metal-free catalysts (Fe, Co, etc.) [6,7], or metal oxide [8], sulphide [9], nitride [10], carbide [11], metal-free carbon based materials [12] and nitrogen-doped carbon [13] have been actively pursued. Among above mentioned catalysts, the application of iron oxide as the electrocatalyst is…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CoÀ N-GVC, the two less intense peaks appeared at the 2θ values of 44.4 and 51.6°are attributed to the CoN x phase (ICDD reference code: 00-041-0943). [30][31][32] Here, it should be noted that the carbide phase is formed in the system along with the grafting of the active center. [27] Similarly, in FeÀ N-GVC, the broad peaks at 43.8 and 44.8°represent the FeN x phase.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29] In the XRD 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 pattern of Fe/2CoÀ N-GVC, two peaks lying closely at the 2θ values of 43.8 and 44.8°are observed; these peaks are assigned to the FeN x and CoN x phases which are expected since the composite contains both Fe and Co as the metal precursors during its synthesis. [30][31][32] Here, it should be noted that the carbide phase is formed in the system along with the grafting of the active center. [33] The carbon framework plays a crucial role in the modulation of the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the elemental composition of the synthesized catalysts, the combined XPS and ICP analysis were performed for every catalyst tested (Table S2). It is found that proper use of Fe amounts in the catalysts is a critical factor affecting the efficiency and the selectivity of the ORR process and the optimal Fe contents for the highly active Fe/N/C catalysts are found to be less than 5 wt.% Fe ,,. Further, experimental Fourier transform at the Fe K‐edge obtained by fitting EXAFS data identified Fe−Fe, Fe−N and Fe−O bond in the prepared Fe/N/C composites (Figure S7).…”
Section: Figurementioning
confidence: 99%